Effect of Climate Change on Acquisition of Quality Education: A Case Study of Maasai Pastoralists in Narok County, Kenya - KORIR, JANET (Advances in Social Sciences Research Journal, 2021)
Climate change is a global phenomenon with far reaching impacts. Arid and semi-arid communities in Kenya, among them the Maasai community from Narok County, are dependent on the natural resources for their livelihood thus are greatly hit by the adverse impacts of climate change. This paper sought to establish the indirect effects of climate change on the quality of education among the Maasai community. Desktop literature review approach and key informant phone interviews were adopted for data collection. The review of literature indicated that increased poverty levels arising from climate change has largely affected the affordability of quality education. Therefore, people in Maasai community resort to coping mechanisms on labour demands that accelerate school dropout as well as early marriages. The Maasai herders are forced to increase their migration trends to long distances, a practice that has increased child labour disrupting learning for most school going children. In addition, the girl child has become more vulnerable to sexual abuse and early marriages with a consequent denial of education opportunities. The effect of the climate change on wildlife habitat has led to human- wildlife conflict that poses a threat to the security of the community members and therefore interferes with the smooth running of schools. Consequently, interventions to mitigate climate change effects should not only concentrate on the direct but also the indirect impacts that have got multiplier effects on sectors like education. These interventions should include, provision of adequate water infrastructure, investment in education policy and boarding school Infrastructural development.